101k views
4 votes
Error Analysis A classmate solves the

equation 8 + 2(8r - 2r) = 4(3r + 2).
She says r = 0 is the only solution. Is
she correct? Explain.

Please need your help

User Indent
by
5.3k points

2 Answers

3 votes
Answer: −12 + 2(6) = −16

Step by step explanation:

1. Combine like terms.

8 + 2(6r) = 4(3r - 2)

2. Distribute.

8 + 2(6r) = 12r - 8

3. Subtract 8 from both sides of the equation.

8 + 2(6r) - 8 = 12r - 8 - 8

4. Simplify

2(6r) = 12r - 6

5. Subtract 12r from both sides of the equation.

2(6r) - 12r = 12r - 6 - 12r

6. Simplify.

-12r + 2(6r) = -16

Solution: -12r + 2(6r) = -16
User Arseniy Zhizhelev
by
4.8k points
6 votes

Answer:

Yes, the student is correct, r is equal to 0.

Explanation:

This equation can be checked by plugging 0 in for each r in the equation.

So we take, 8+2(8r-2r)=4(3r+2) and apply 0 to the r's. Which results in:

8+2(8(0)-2(0))=4(3(0)+2)) Using pemdas, we know to work within the parenthesis first. 8*0 is equal to 0, and 2*0 is equal to 0. Now we have 8+2(0-0)=4(3(0)+2)). 0 minus 0 is 0. 8+2(0)=4(3(0)+2)) Next, we can work within the parenthesis on the right side of the equation. Therefore, 3*0 is 0, and 0 plus 2 equals 2. Now our equation looks like 8+2(0)=4(2). Next we check for exponents (pEmdas), and find none so we can move onto multiplication (peMdas). We can multiply 2*0 to get 0, and 4*2, which equals 8. Our equation now looks like 8+0=8. Moving on to division (pemDas), which is not present, leads us to addition(pemdAs). 8 plus 0 equal 8, meaning our final equation is 8=8. meaning the student is correct and r=0.

User Adam Gritt
by
5.0k points